2021
DOI: 10.1002/sctm.20-0289
|View full text |Cite
|
Sign up to set email alerts
|

Resident vs nonresident multipotent mesenchymal stromal cell interactions with B lymphocytes result in disparate outcomes

Abstract: Multipotent human mesenchymal stromal cells (MSCs) from multiple organs including the bone marrow (BM) and placenta harbor clinically relevant immunomodulation best demonstrated toward T lymphocytes. Surprisingly, there is limited knowledge on interactions with B lymphocytes, which originate from the BM where there is a resident MSC. With increasing data demonstrating MSC tissue‐specific propensities impacting therapeutic outcome, we therefore investigated the interactions of BM‐MSCs—its resident and “niche” M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Interestingly, immunomodulatory paracrine factors such as PGE 2 and IDO inducible by inflammatory signals including IFN‐γ and IL‐1β are prominent in MSC interactions across leukocyte subpopulations including all lymphoid cells including T cells, NKs, 20 and B cells in which IL‐10‐expressing regulatory B cells are expanded 21,22 . Reports are most scarce for MSC‐B cell interactions, but most demonstrate suppression of B cell proliferation, differentiation, and antibody production 23‐29 ; our recent report found that MSC‐B cell interactions may be more complex than previously thought due to MSC source‐specific differences in expression of relevant factors 30 . Such information on tissue‐specific MSC properties may provide insights which could prove relevant for clinical application 11,31 …”
Section: Brief Summary On Preclinical Evidence Of Msc Immunomodulatory Mechanismsmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, immunomodulatory paracrine factors such as PGE 2 and IDO inducible by inflammatory signals including IFN‐γ and IL‐1β are prominent in MSC interactions across leukocyte subpopulations including all lymphoid cells including T cells, NKs, 20 and B cells in which IL‐10‐expressing regulatory B cells are expanded 21,22 . Reports are most scarce for MSC‐B cell interactions, but most demonstrate suppression of B cell proliferation, differentiation, and antibody production 23‐29 ; our recent report found that MSC‐B cell interactions may be more complex than previously thought due to MSC source‐specific differences in expression of relevant factors 30 . Such information on tissue‐specific MSC properties may provide insights which could prove relevant for clinical application 11,31 …”
Section: Brief Summary On Preclinical Evidence Of Msc Immunomodulatory Mechanismsmentioning
confidence: 88%
“…Close attention should be paid to trial results for psoriasis, also a predominately Th17 disease, which have been numerous recently. Another variable to follow closely is whether different sources of MSCs would be particularly suited to specific diseases, since preclinical results are starting to indicate tissue‐specific differences in MSC immunomodulatory mechanisms 30,48 …”
Section: Current Clinical Trials Of Msct For Immune‐related Diseases: Specific Indicationsmentioning
confidence: 99%
“…Single-cell suspensions derived from lung lobes were stained with antibodies recognising CD45, CD11b, F4/80, CD206, inducible nitric oxide synthase (iNOS), arginase-1 (Arg1), TNF-α (all from eBioscience, San Diego, California, USA), or 2′,7′-dichlorofluorescein diacetate (DCFDA, Sigma-Aldrich, Missouri, USA) for 30 min according to manufacturer’s instructions, then assessed by flow cytometry or analysed with t-distributed stochastic neighbor embedding (t-SNE)-based algorithm 20 21…”
Section: Methodsmentioning
confidence: 99%
“…In a mouse model of colitis, intraperitoneal injection of BMMSCs could regulate the immunomodulatory effects of B cells by upregulating IL-10 expression, induce a regulatory B-cell (Breg) population characterized by CD23 and CD43 phenotypic markers, increase the number of CD23 + , CD43 + , and Breg cells, reduce the clinical and pathological severity of colitis in mice ( Chen et al, 2019a ). Researchers studied the interactions of BM-MSCs and placental MSCs (P-MSCs) in the mouse model, found that P-MSCs could inhibit the proliferation and further differentiation of B cells ( Lee et al, 2021 ).…”
Section: Modulation Of Different Immune Cells By Mesenchymal Stem Cellsmentioning
confidence: 99%